The role of artificial intelligence data in estimating the extent of gully erosion the basin is Wadi Khashm Al-Mujadar - Al-Abru, Duha Jawad Kazem; Al-Moardah, Prof. Dr. Hussain Joban Uraybi (South Eastern European Journal of Public Health, 2024)
Wadi Khashm Al-Mujadar basin is one of the dry valleys in the southern western plateau of Iraq, it is located astronomically between two latitudes (5314.191◦29) (2437.944◦29) north, and (102.327◦46) (02.79◦46) east. It is characterized by geomorphological, hydrological and natural resource characteristics, contributes to the development of the lands of the southern Western Plateau. The importance of the topic comes from the natural and human characteristics of this basin that contribute to development, with artificial intelligence data, it has become an important tool in the process of analyzing, linking, interpreting and modeling some natural risks, to which the soil and lands are exposed under varying climatic conditions that contribute to the variation in the quality and extent of erosion. The use of artificial intelligence data is an effective tool in achieving valuable and accurate results. The research aims to use artificial intelligence data to estimate the extent of erosion, determine its type, cases, and degree of severity, and model it, depending on the results of the calibrations used, especially the Bergsma criterion for determining groove erosion. Gully erosion in the basin varies from light gully erosion to high gully erosion, due to the variation in the amount of rain, its falling regime, and the characteristics of the soil in the region, in addition to the rock formations, the steepness of the slope, the density of natural vegetation and the role of humans in it. The study showed that there are (4) erosion zones: it is a very light erosion zone(13.03 km2 and a rate of 4.28%), the area of light erosion (218.35 km2, at a rate of 71.81%, the moderate erosion zone (68.71 km2, at a rate of 22.6%, and the high erosion zone (3.99 km2, at a rate of 1.31%. The majority of the area was located within the range of light and moderate erosion, requires finding ways to reduce soil erosion and the deterioration of its structure, composition and natural properties.